Kajian Faktor Determinan terhadap Pengetahuan dan Sikap Ibu Hamil Trimester III dalam Penggunaan Buku KIA Di Kabupaten Karawang - Irna Trisnawati; Jundra Darwanty (FORIKES, 2020)
Coverage of MCH Handbook in Karawang district in 2016 was 67.3%, while coverage of pregnant women with K1 reached 89.4%. The research objective is to determine the determinant factors that influence the knowledge and attitudes of third trimester pregnant women towards the use of the MCH handbook in Karawang Regency. The research used analytical research type with cross sectional design. Population and sample of third trimester pregnant women were in Karawang. Sample size were 104 respondents, accidental sampling technique. Data analysis included descriptive and bivariate with a Chi square test. The majority of respondents had better knowledge of 62.5%, had a negative attitude of 55.8%, aged ≥28 were 53.8%, low education 63.5%, not working 83.7%, multigravida 77.9 %, and frequency ≥4 times as much as 79.8%. The results of the bivariate study of all independent variabels after the Chi square test with knowledge and attitude variabels have a value of p>0.005. There was no relationship between age, education, gravida and frequency of visits with the knowledge and attitudes of third trimester pregnant women regarding the use of the MCH handbook. Although statistically meaningless, the use of the MCH handbook must still be done by increasing the quality of utilization both by pregnant women and by health workers. Keywords: MCH handbook; trimester III pregnant women; knowledge; attitude ABSTRAK Cakupan Buku KIA di kabupaten Karawang tahun 2016 adalah 67,3%, sedangkan cakupan ibu hamil dengan K1 mencapai 89,4%. Penelitian ini bertujuan untuk mengetahui hubungan faktor determinan dengan pengetahuan dan sikap ibu hamil trimester III terhadap penggunaan buku KIA di Kabupaten Karawang. Jenis penelitian ini adalah analitik dengan desain cross sectional. Populasi dan sampel ibu hamil trimester III di wilayah Karawang. Ukuran sampel 104 responden, teknik pengambilan sampel adalah accidental sampling. Analisis data meliputi deskriptif dan bivariat dengan uji Chi square. Sebagian besar responden berpengetahuan baik yaitu 62,5%, memiliki sikap negatif 55,8%, berumur ≥28 sebanyak 53,8%, pendidikan rendah 63,5%, tidak bekerja 83,7%, multigravida 77,9%, dan frekuensi ≥4 kali sebanyak 79,8%. Hasil penelitian bivariat menunjukan bahwa semua variabel independen setelah diuji Chi square dengan variabel pengetahuan dan sikap memiliki nilai p>0,005. Tidak ada hubungan antara umur, pendidikan, gravida dan Frekuensi kunjungan dengan pengetahuan dan sikap ibu hamil trimester III tentang penggunaan buku KIA. Walaupun secara statistic tidak bermakna, namun pengunaan buku KIA tetap harus dilakukan dengan meningkatkan kualitas pemanfaatan baik oleh ibu hamil maupun oleh tenaga kesehatan. Kata kunci: buku KIA; pengetahuan ibu hamil trimester III; sikap ibu hamil trimester III